Peran Mediasi Mimicry Desire Dalam Hubungan Antara Kredibilitas dan Kesamaan Food Vlogger Dengan Purchase Intention Viewer: The Mediating Role of Mimicry Desire in The Relationship Between Food Vloggers’ Credibility and Similarity With Viewers' Purchase Intention - Given, Lovia; Ardianti, Retno (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
With the rising popularity of food vlogger in Indonesia, extant studies have not examined the effect of watching their content on viewers’ intention to mimic vloggers’ behaviors and to buy food products that they recommend. Therefore, in this study, we aim to examine the role of mimicry desire as the mediating variable that explains the relationship between food vlogger's credibility and similarity (homophily) on viewer's purchase intention. By using convenience sampling method, this study uses data obtained from an online survey to the viewers of well-known Indonesian food vlogger on Youtube. Further, by using PLS-SEM in the data analysis, our results indicate the positive role of credibility, homophily, and mimicry desire in explaining viewers’ purchase intention. In addition, our result show the role of mimicry desire as a full mediating variable in explaining the relationship between similarity (homophily) on purchase intention. Keywords: food vlogger, mimicry desire, purchase intention, Youtube, homophily